DOKTER DI LAYANAN PRIMER DENGAN PENDEKATAN KEDOKTERAN KELUARGA DALAM SISTEM PELAYANAN KESEHATAN - Hendra kurniawan (Universitas Syiah Kuala, 2015)
Abstrak :Tujuan pembangunan nasional adalah dengan tersedianya sistem pelayanan kesehatan yang efektif, berkualitas dan tepat sasaran. Pelayanan kesehatan yang baik dan merata hendaknya memenuhi segi ketersedian, penerimaan, keterjangkauan dan mutu yang baik. Dokter praktik umum sebagai tenaga kesehatan diupayakan untuk menjadi tulang punggung dan menangani masalah kesehatan secara paripurna pada layanan primer. Ilmu Kedokteran Keluarga dapat diterapkan dalam melakukan pelayanan. Arah kebijakan pemerintah dalam memperkuat sistem layanan primer telah tertuang dalam bentuk Undang-undang dan dibutuhkan komitmen dari semua pihak dalam pelaksanaannya.Abstract :The achievement of national development is the availability of an effective health care system, qualified and Objective of national development is the availability of an effective health care system, qualified and targeted. Good health care and equitable terms should meet the availability, acceptance, affordability and good quality. General practitioners as health workers strived to become the backbone and addressing health issues in plenary on primary care. Family Medical science can be applied in performing the service. The direction of government policy in strengthening the primary care system has been stipulated in the legislation and required commitment from all parties in the implementation. The good health care should provide the availability, acceptance, affordability and good quality. The physicians as health care workers strived to become the backbone and addressing health problem in plenary on primary care. Family medicine science could be be applied in performing the service. The direction of government policy in strengthening the primary care system has been stipulated in the legislation and required commitment from all parties in the implementation.